2019
DOI: 10.1111/tpj.14456
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and reactive carbonyl species constitute a feed‐forward loop in auxin signaling for lateral root formation

Abstract: Summary In auxin‐stimulated roots, production of reactive oxygen species (ROS) via the hormone‐induced activation of respiratory burst oxidase homologous NADPH oxidases facilitates lateral root (LR) formation. In this study, in order to verify that ROS can modulate auxin signaling, we examined the involvement of the lipid peroxide‐derived agents known as reactive carbonyl species (RCS) in LR formation. When auxin was added to Arabidopsis thaliana roots, the levels of RCS, for example acrolein, 4‐hydroxynonenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 71 publications
0
58
3
Order By: Relevance
“…Despite the understanding that auxin induces ROS production to regulate cell elongation (Schopfer, 2001) and root gravitropism (Joo et al, 2001), the molecular relationship between ROS and auxin remains largely unknown. Recent study revealed the potential feed-forward loop between ROS and auxin signaling to control lateral root formation (Biswas et al, 2019). It was confirmed that production of reactive oxygen species (ROS) via the hormone-induced activation of respiratory burst oxidase homologous NADPH oxidases facilitates lateral root (LR) formation, and that the auxin-induced production of ROS and their downstream products RCS (reactive carbonyl species) modulate the auxin signaling pathway in a feed-forward manner.…”
Section: Ros Interact With Other Signaling Hormones To Regulate Root mentioning
confidence: 93%
See 2 more Smart Citations
“…Despite the understanding that auxin induces ROS production to regulate cell elongation (Schopfer, 2001) and root gravitropism (Joo et al, 2001), the molecular relationship between ROS and auxin remains largely unknown. Recent study revealed the potential feed-forward loop between ROS and auxin signaling to control lateral root formation (Biswas et al, 2019). It was confirmed that production of reactive oxygen species (ROS) via the hormone-induced activation of respiratory burst oxidase homologous NADPH oxidases facilitates lateral root (LR) formation, and that the auxin-induced production of ROS and their downstream products RCS (reactive carbonyl species) modulate the auxin signaling pathway in a feed-forward manner.…”
Section: Ros Interact With Other Signaling Hormones To Regulate Root mentioning
confidence: 93%
“…•− and H 2 O 2 accumulate in the meristematic and elongation zones, respectively (Dunand et al, 2007;Biswas et al, 2019). An imbalance will lead to a change in the size of the meristematic zone.…”
Section: Gradient Distribution Of Ros Regulates Root Stem Cell Differmentioning
confidence: 99%
See 1 more Smart Citation
“…RCS is a group name of the α,β-unsaturated aldehydes and ketones, such as acrolein and 4-hydroxy-(E)-2-nonenal (HNE) [13,14]. RCS are generated from lipid peroxides (LOOH) and act as agents to mediate ROS signal to target proteins in the heat shock-responsive gene regulation [15], senescence [16], abscisic acid (ABA) signaling for stomatal closure [17,18], and auxin signaling for lateral root formation [19] in plants. We reported that tobacco BY-2 cells exposed to H 2 O 2 generated acrolein and HNE, and a chemical carbonyl scavenger prevented the initiation of PCD, without affecting the increase in the intracellular ROS level [12].…”
Section: Introductionmentioning
confidence: 99%
“…In order to maintain normal growth under adverse conditions, plants must be able to readily remove ROS, preventing the damage to cellular components and cellular structures (Biswas et al 2019). In S. salsa, the photochemistry in photosystem II did not change when the plants were grown under high-salinity conditions (100-400 mM NaCl), indicating that high salinity did not affect the photosynthetic apparatus (Lu et al 2002).…”
Section: Regulation Of Antioxidant Levels During Seedling Growthmentioning
confidence: 99%